2017
DOI: 10.1111/jvim.14724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Weight Change During Carboplatin Therapy in Dogs With Appendicular Osteosarcoma

Abstract: BackgroundThe prevalence of cancer cachexia in veterinary medicine has not been studied widely, and as of yet, no definitive diagnostic criteria effectively assess this syndrome in veterinary patients.Objectives(1) To determine the patterns of weight change in dogs with appendicular osteosarcoma treated with amputation and single‐agent carboplatin during the course of adjuvant chemotherapy; and (2) to determine whether postoperative weight change is a negative prognostic indicator for survival time in dogs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[7, 20] However, the radius has been more frequently reported as the most common site for canine OS. [2, 3, 14, 16, 18, 25, 26, 28] The category of “radius/ulna” as a tumor location in this study may have affected the accuracy of the evaluation of tumor location frequency, as this category included tumors whose bone of origin (radius versus ulna) could not be clearly distinguished from the medical record, and thus were not included in the analysis for location frequency. Exclusion of the 54 cases arising in this area may have led to under-estimation of the distal radius as an anatomic site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7, 20] However, the radius has been more frequently reported as the most common site for canine OS. [2, 3, 14, 16, 18, 25, 26, 28] The category of “radius/ulna” as a tumor location in this study may have affected the accuracy of the evaluation of tumor location frequency, as this category included tumors whose bone of origin (radius versus ulna) could not be clearly distinguished from the medical record, and thus were not included in the analysis for location frequency. Exclusion of the 54 cases arising in this area may have led to under-estimation of the distal radius as an anatomic site.…”
Section: Discussionmentioning
confidence: 99%
“…[24, 8, 10, 12–16] Males have been over-represented in some reports but this finding has not been supported in other reports. [2, 3, 710, 12–18] Endogenous sex hormones may play a role in sarcomagenesis–some studies have identified significantly increased risk of developing OS in neutered compared to intact dogs. [13, 1921] Appendicular OS has been commonly reported in large and giant breed dogs, with increased incidence of disease in certain breeds including boxers, Great Danes, Rottweilers, Saint Bernards, Irish setters, Doberman pinschers, greyhounds, German shepherds, Irish wolfhounds and Leonbergers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few animal studies have examined the metabolic impact of chemotherapy; Story et al reported weight gain in dogs receiving carboplatin while another study found significant increases in total and LDL cholesterol in rats when treated with cisplatin and oxaliplatin . Pivotal studies on humans have linked alkylating agents to hypertension and increased cholesterol, but metabolic factors are rarely part of initial drug testing.…”
Section: Introductionmentioning
confidence: 99%